2014
DOI: 10.1038/srep04144
|View full text |Cite
|
Sign up to set email alerts
|

Impact of better and worse eye damage on quality of life in advanced glaucoma

Abstract: The purpose of the study was to investigate the influence of VF and the VA on vision related quality of life (VRQoL) in advanced glaucoma. Subjects consist of 50 glaucoma patients with mean deviation (MD) less than −20 dB in at least one eye. Patients' VRQoL was assessed using the ‘Sumi questionnaire’. The impact of seven visual measures on VRQoL were compared using principal component regression: MDs of better and worse eyes with 10-2 and 24-2 Humphrey VFs, LogMAR VAs of better and worse eyes and the Esterman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 45 publications
3
13
0
1
Order By: Relevance
“…Our finding that correlation with the NEI VFQ-25 scores was stronger for VFI than for MD agrees with results reported by Sawada et al (2011). The association with VRQOL was weaker for VF loss in the worse eye than for VF loss in the better eye (results not shown), which also concurs with other studies (van Gestel et al 2010;Sawada et al 2011;Okamoto et al 2014). Better-eye VA showed the strongest correlation with VRQOL, and better-eye VA and better-eye VFI together explained nearly 40% of the Raschcalibrated NEI VFQ-25 scores.…”
Section: Visual Function At Final Visitsupporting
confidence: 92%
See 2 more Smart Citations
“…Our finding that correlation with the NEI VFQ-25 scores was stronger for VFI than for MD agrees with results reported by Sawada et al (2011). The association with VRQOL was weaker for VF loss in the worse eye than for VF loss in the better eye (results not shown), which also concurs with other studies (van Gestel et al 2010;Sawada et al 2011;Okamoto et al 2014). Better-eye VA showed the strongest correlation with VRQOL, and better-eye VA and better-eye VFI together explained nearly 40% of the Raschcalibrated NEI VFQ-25 scores.…”
Section: Visual Function At Final Visitsupporting
confidence: 92%
“…Some authors advocate using binocular VF results to evaluate VRQOL, because monocular measures might overestimate VF loss (Asaoka et al 2011), and patients with overlapping VF loss might experience more difficulties in everyday life (Coleman 2007). However, the results of other cross-sectional studies indicate that evaluating the VF of the better eye provides information similar to data obtained by binocular assessment (Kulkarni et al 2012;Saunders et al 2012) and that the association between VRQOL and better-eye MD is similar to the association between VRQOL and binocular VF (McKean-Cowdin et al 2008;Ramulu 2009;van Gestel et al 2010;Arora et al 2013;Okamoto et al 2014). In the Collaborative Initial Glaucoma Treatment Study, Musch et al (2006) found that patients with glaucoma had better VRQOL after cataract surgery.…”
Section: Visual Function At Final Visitmentioning
confidence: 57%
See 1 more Smart Citation
“…MD value is one of the most frequently used global indices representing the overall depression and it is used in the studies regarding the intereye comparison in glaucoma patients. 16,26,27 However, the functional glaucomatous damage can be defined by several other ways, such as by area, depth of loss, or location of damages, and these localized VF damage might be inadequately described by the MD measurement. In addition, only the Average RNFL versus MD of worse eyes and better eyes, (C, D) inferior RNFLT versus superior VF of worse eyes and better eyes, (E, F) superior RNFLT versus inferior VF of worse eyes and better eyes, and (G, H) average GCIPLT versus central VF of worse eyes and better eyes.…”
Section: Discussionmentioning
confidence: 99%
“…У водителей с глаукомой частота аварий в 1,65 раза выше, чем в группе контроля, даже после поправки на возраст и психическое состояние [30]. Наиболее значимыми проблемами пациентов с глаукомой, взаимосвязанными с качеством жизни, названы расплывчатое зрение (32 %), проблемы при чтении мелкого шрифта (34 %), объем медицинских расходов (26 %) и сухость глаза (32 %) [31,32]. Опасения по поводу зрения коррелировали с изменениями границ периферического зрения лучшего и худшего глаз.…”
Section: Modern Multicenter Studies Of Psychological Features Proper unclassified